Pengaruh Stratifikasi Sosial dalam Pendidikan Islam : Kajian Literatur dan Perspektif Historis - Latifatus Sakdiyah; Anggi Eka Permadani; Fatihah Naufala Yusifatul Azizah; Mualimin Mualimin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This article explores the impact of social stratification on Islamic education through a comprehensive literature review and a historical perspective. It identifies key themes such as access to education, socio-economic disparities, and the role of cultural norms within Islamic societies. The historical context is essential for understanding how various socio-economic classes have influenced educational practices and structures over time. The findings indicate that social stratification has significantly shaped educational opportunities, curriculum development, and the overall effectiveness of Islamic educational institutions. This article aims to highlight the complex interplay between social hierarchy and educational access, providing recommendations for enhancing equity in Islamic education.